The impact of CLIL technology on the professional competence of pre-service biology teachers (Journal of Educational Sciences, 2024)
The article examines the impact of content and language integrated learning (clil) technology on students enrolled in the educational program of teacher training in biology. according to the results of the study, conducted on the formation of professional competence of a future biology teacher, the effectiveness of the use of clil technology in biology lessons taught in english is theoretically justified.the article presents the results of a survey conducted to assess the perception of integrated learning technology by senior students in the context of higher education. the students’ understanding of the essence of clil technology, the duration of its use, the advantages and difficulties associated with the application, as well as the impact on the formation of professional competencies of pre-service biology teachers are analyzed. students of u.zhanibekov  south kazakhstan pedagogical university took part in the survey. the survey results revealed the prospects and difficulties related to the introduction of clil technology into the educational process of universities. clil classes cannot completely replace the biology lesson taught in the native language, but can only complement it. integrated teaching of biology with a foreign language is an effective way to implement a trilingual education program.  the article gives important recommendations to future teachers and researches in the field of education and intercultural communication. Keywords: CLIL technology, integrated teaching of a foreign language, pre-service biology teacher, methodological approaches, multicultural personality.